Comparative study of a normal solar water heater and smart thermal/thermoelectric hybrid systems. (2020) - Faddouli, Ali; Fadili, Salah; Labrim, Hicham; Hartiti, Bouchaib; Ertugrul, Mehmet; Belouaggadia, Nawal; Stitou, Mohamed
Abstract: A comparative numerical study between a normal solar water heater and two hybrid systems have been presented. The first system constituted by solar water heater integrating a planar thermoelectric generator and the other one composed by the thermal device, tubular and planar thermoelectric generators. The computational model consisted to describe the behavior of each component for any device, based on the Finite-Difference Method coded in MATLAB software. The results indicate that how the presented coupled system improved the performance and the quantity of hot water stored and the benefits of using TEG to generating additional electrical energy, which very interesting in the cogeneration and the hybrid systems development.